Resource Windfalls and Emerging Market Sovereign Bond Spreads : The Role of Political Institutions - Arezki, Rabah; Brückner, Markus (World Bank, 2013)
We examine the effect that revenue windfalls from international commodity price booms have on sovereign bond spreads using panel data for 38 emerging market economies during the period 1997-2007. Our main finding is that commodity price booms lead to a significant reduction in the sovereign bond spread in democracies, but to a significant increase in the spread in autocracies. To explain our finding we show that, consistent with the political economy literature on the resource curse, revenue windfalls from international commodity price booms significantly increased real per capita GDP growth in democracies, while in autocracies GDP per capita growth decreased.